Mapping the evolution and research landscape of ferroptosis-targeted nanomedicine: insights from a scientometric analysis - Cao, Siyang; Wei, Yihao; Yue, Yaohang; Wang, Deli; Yang, Jun; Xiong, Ao; Zeng, Hui (Frontiers in Pharmacology, 2024)
Objective: Notable progress has been made in "ferroptosis-based nano drug delivery systems (NDDSs)" over the past eleven years. Despite the ongoing absence of a comprehensive scientometric overview and up-to-date scientific mapping research, especially regarding the evolution, critical research pathways, current research landscape, central investigative themes, and future directions. Methods: Data ranging from January 1, 2012, to November 30, 2023, were obtained from the Web of Science database. A variety of advanced analytical tools were employed for detailed scientometric and visual analyses. Results: The results show that China significantly led the field, contributing 82.09% of the total publications, thereby largely shaping the research domain. Chen Yu emerged as the most productive author in this field. Notably, the journal ACS Nano had the greatest number of relevant publications. The study identified liver neoplasms, pancreatic neoplasms, gliomas, neoplasm metastases, and melanomas as the top five crucial disorders in this research area. Conclusion: This research provides a comprehensive scientometric assessment, enhancing our understanding of NDDSs focused on ferroptosis. Consequently, it enables rapid access to essential information and facilitates the extraction of novel ideas in the field of ferroptotic nanomedicine for both experienced and emerging researchers.